Efisiensi dan Efektivitas Pembiayaan Pendidikan serta Dampaknya terhadap Mutu Sekolah Dasar di Era Otonomi Daerah: A Systematic Literature Review - Sitepu, Eva Rosdiana Br; Adawiyah, Robiatul; Muliani, Evi; Mulawarman, Widyatmike Gede; Nurhadi, Mukhamad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the efficiency and effectiveness of education financing and its impact on the quality of primary schools in the era of regional autonomy using a Systematic Literature Review (SLR) approach. The background of this study is based on the increasing demand for accountability in the management of education budgets, as well as disparities in educational quality across regions as a consequence of decentralization policies. The method employed follows the SLR procedure, including identification, screening, and synthesis of scholarly articles published between 2021 and 2026 from major academic databases. A total of 20 articles that met the inclusion criteria were analyzed using thematic analysis to identify patterns in the relationship between education financing and primary school quality.The findings reveal that the efficiency of education financing is more determined by the quality of school management in utilizing resources rather than the amount of funding available. The effectiveness of financing is strongly correlated with transparency and accountability in financial management, which ensures the appropriate allocation of funds. Furthermore, the impact of education financing on school quality is indirect (indirect effect), mediated by factors such as teacher performance, school leadership, and the quality of the learning process. The study also finds that regional autonomy leads to disparities in education financing and school quality due to differences in fiscal capacity and managerial competence across regions.In conclusion, increasing education funding does not automatically improve the quality of primary schools without effective governance and adequate managerial capacity. Therefore, strengthening financial management systems, enhancing transparency and accountability, and implementing equity-oriented policies are essential to ensure the effectiveness of education financing in the era of regional autonomy.